Inside Cover: Formation of RNA Phosphodiester Bond by Histidine‐Containing Dipeptides (ChemBioChem 2/2013). Issue 2 (17th January 2013) - Wieczorek, Rafał; Dörr, Mark; Chotera, Agata; Luisi, Pier Luigi; Monnard, Pierre‐Alain
<x xml:space="preserve">Abstract</x> The inside cover picture shows the oligomerization of activated RNA monomers by the catalytic dipeptide Ser‐His. On p. 217 ff., P.‐A. Monnard et al. explain how the reaction takes place in a water/ice eutectic phase below 0 °C. This reaction environment is believed to be prebiotically plausible and likely present today on various planetary bodies like the moon Europa (background photograph: NASA, http://photojournal.jpl.nasa.gov).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>